Prognostic value of right ventricular free wall strain in patients with sepsis - Chen, Hongmin; Huang, Lei; Xing, Boyuan; Gao, Yang; Zhang, Jie; Zhang, Bingyi (Frontiers in Cardiovascular Medicine, 2024)
Background Right ventricular systolic dysfunction (RVSD) in patients with sepsis is an area of growing interest, but its prognostic significance remains unclear and additional tools are needed to improve our understanding. Right ventricular free wall strain (RV-FWS) is a relatively new parameter to assess RV function. This study aimed to investigate the potential correlation between impaired RV-FWS and prognostic outcomes in patients with sepsis. Methods We prospectively assessed right ventricular function in patients with sepsis within the initial 24 h of their hospital admission. RV-FWS, right ventricular global strain (RV-GS), fractional area change (FAC), and tricuspid annular plane systolic excursion (TAPSE) were examined. RVSD was defined as impaired RV-FWS. Moreover, the association between RVSD and 30-day mortality rate was assessed. Results This study included 89 patients. Among them, 27 (30.3%) succumbed to their illness within 30 days. The nonsurviving patients demonstrated significantly lower absolute RV-FWS (−19.7% ± 2.4% vs. −21.1% ± 2.1%, P = 0.008) and RV-GS (−17.7% ± 1.2% vs. −18.4% ± 1.4%, P = 0.032) values than the surviving patients. However, TAPSE and FAC values were not significantly different between the two groups. The optimal cutoff values for RV-FWS, RV-GS, FAC, and TAPSE were −19.0%, −17.9%, 36.5%, and 1.55 cm, respectively. Kaplan–Meier survival curves revealed that patients with impaired RV-FWS and RV-GS demonstrated lower 30-day survival rates, and the predictive performance of RV-FWS (hazard ratio [HR]: 3.97, 95% confidence interval [CI]: 1.85–8.51, P < 0.001) was slightly higher than FAC and TAPSE. However, multivariable Cox regression analysis revealed no association between impaired RV-FWS and mortality outcomes (HR: 1.85, 95% CI: 0.56–6.14, P = 0.316). Conclusions Impaired RV-FWS is not associated with short-term mortality outcomes, and RV strain imaging is of limited value in assessing the prognosis of sepsis.